2017
DOI: 10.1002/14651858.cd006096.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating lymphocytic colitis

Abstract: Background Lymphocytic colitis is a cause of chronic diarrhea. It is a subtype of microscopic colitis characterized by chronic, watery, non-bloody diarrhea and normal endoscopic and radiologic findings. The etiology of this disorder is unknown.Therapy is based mainly on case series and uncontrolled trials, or by extrapolation of data for treating collagenous colitis, a related disorder. This review is an update of a previously published Cochrane review. Objectives To evaluate the efficacy and safety of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 70 publications
0
17
0
3
Order By: Relevance
“…A recent 2017 Cochrane review echoed these sentiments and demonstrated that budesonide 9 mg/day for 6–8 weeks was effective in inducing both clinical and histologic remission. In two examined studies with a total of 57 patients, 88% showed clinical response to budesonide as opposed to 38% to placebo and 78% showed histologic response compared with 33% with placebo 50. The “number needed to treat” was two for CC and three for LC.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent 2017 Cochrane review echoed these sentiments and demonstrated that budesonide 9 mg/day for 6–8 weeks was effective in inducing both clinical and histologic remission. In two examined studies with a total of 57 patients, 88% showed clinical response to budesonide as opposed to 38% to placebo and 78% showed histologic response compared with 33% with placebo 50. The “number needed to treat” was two for CC and three for LC.…”
Section: Managementmentioning
confidence: 99%
“…At week 8, 70% of patients were in remission 55. While beclomethasone does appear to induce remission, a 2010 trial demonstrated that only 26% of patients (from the 84% with initial response) maintained clinical remission at 1 year, bringing its longevity into question 50. While beclomethasone dipropionate is promising, it is not available in the USA and to date is only in use in Europe.…”
Section: Managementmentioning
confidence: 99%
“…Treatment is guided by response to symptoms, with budesonide identified as the most effective drug to control MC (19)(20)(21). Unfortunately, as reported by Mihaly et al not enough data have been received from extensive trials on alternative drugs including immunomodulators, aminosalicylates, and biological treatment such as TNF-alpha antagonists and integrin inhibitors.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…The controlled-release formulations of oral budesonide are proven both effective and well tolerated in patients with ileoceacal CrohnÂŽs disease 1,2 and have been a breakthrough in the treatment of microscopic colitis (MC). 3,4 Unlike most other oral corticosteroids, budesonide has a substantial first-pass metabolism. Thereby, it exerts an immunosuppressant effect in the gut wall and is subsequently metabolised in the liver, thus resulting in quite a low systemic bioavailability, about 10% 1 compared to more than 80% for prednisolone.…”
Section: Introductionmentioning
confidence: 99%
“…5 This ingenious leveraging of first-pass metabolism has enabled us to use budesonide for maintenance treatment of MC without undue toxicity. 3,4 However, adverse effects related to long-term use of corticosteroids are of concern. Oral corticosteroids in general are known to increase the risk of osteoporotic fractures through a reduction in bone formations and osteocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%